CUSTOMER LIFETIME VALUE METRICS AS CUSTOMER RELATIONSHIP MANAGEMENT INDICATORS - Kurniawan, Alief Reza; Mayasari, Riana; Febriantoko, Jovan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The use of CLV can assist companies in making management decisions in determining the most profitable strategy for the company. The formulation of the problem in this study is related to the analysis of the strategy applied by PTTWJ in CRM using one of the CRM metrics, namely CLV. The purpose of this study was to analyze the strategies that must be applied in managing customers and identify the factors causing the decline in visitors. The method used in this research was descriptive qualitative with a case study approach. Data collection techniques used in this study were in-depth interviews, documentation, observation and literature study. The types of data used in this study were primary and secondary data. Primary data obtained from in-depth interviews and observations. Secondary data obtained from documentation and literature study. Credibility test using triangulation and member check. Data analysis was inductive by drawing conclusions from data or events through interviews, documentation, observations, and calculations. Based on the results of data analysis, it is known that there is a decrease in the value of CLV in all categories. It is because the company only implements CRM in a simple and not optimal way.